Java programming : - Fain, Yakov (Wiley Publishing, Inc., 2015)
Java Programming 24-Hour Trainer, 2nd Edition is your complete beginner's guide to the Java programming language, with easy-to-follow lessons and supplemental exercises that help you get up and running quickly. Step-by-step instruction walks you through the basics of object-oriented programming, syntax, interfaces, and more, before building upon your skills to develop games, web apps, networks, and automations. This second edition has been updated to align with Java SE 8 and Java EE 7, and includes new information on GUI basics, lambda expressions, streaming API, WebSockets, and Gradle. Even if you have no programming experience at all, the more than six hours of Java programming screencasts will demonstrate major concepts and procedures in a way that facilitates learning and promotes a better understanding of the development process.